Constructivist Didactics in the Teaching-Learning Process - Núñez-Naranjo, Aracelly (2022)
This paper reflects on the applicability of didactics in the constructivist approach, derived from different ideologies and worldviews associated with the teaching-learning process, based on the analysis of the tradition of educational practices in the classroom, as well as the characteristics adopted by teachers in the applicability of the curriculum, within the comprehensive training. The methodology was based on the systemic bibliographic review and in which the performance responds to the questions what, how and when to teach. The results show that there are different didactic strategies aimed at constructivism. Reference is also made to constructivist didactics as an organized and complex activity, in which the learner constructs their own learning, through interest, previous learning and transformations. It is concluded that the evolution of education has undergone significant transformations, where the passivity of the learner assumes a role in innovation and creativity.